2005
DOI: 10.1103/physrevb.71.060401
|View full text |Cite
|
Sign up to set email alerts
|

Weak ferromagnetism and magnetoelectric coupling in bismuth ferrite

Abstract: We analyze the coupling between the ferroelectric and magnetic order parameters in the magnetoelectric multiferroic BiFeO 3 using density functional theory within the local spin density approximation ͑LSDA͒ and the LSDA+ U method. We show that weak ferromagnetism of the Dzyaloshinskii-Moriya type occurs in this material, and we analyze the coupling between the resulting magnetization and the structural distortions. We explore the possibility of electric-field-induced magnetization reversal and show that, altho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

61
990
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,414 publications
(1,053 citation statements)
references
References 30 publications
(38 reference statements)
61
990
1
1
Order By: Relevance
“…10 In the absence of cycloidal spin order, as is achieved both in BiFeO 3 thin films 1 and isovalently substituted BiFe 1−x Mn x O 3 , 7 linear magnetoelectric effects in the noncentrosymmetric phases of BiFeO 3 related ceramics become symmetry allowed and activate by a coupling between the A-site ferroelectric translation and the B-site magnetization via the antiferrodistortive a − a − a − tilt of the oxygen octahedra. 11 Although the linear magnetoelectric effect is symmetry forbidden on a macroscopic scale, the DzyaloshinskiiMoriya mechanism can still be used locally in bulk BiFeO 3 to achieve an electric switching of the spin cycloid. 12 Upon isovalent substitution on the A site, disorder is introduced which eventually leads to a decoherence of the Bi lone pair and a concurrent change in space group from the polar R3c to a nonpolar space group.…”
Section: Introductionmentioning
confidence: 99%
“…10 In the absence of cycloidal spin order, as is achieved both in BiFeO 3 thin films 1 and isovalently substituted BiFe 1−x Mn x O 3 , 7 linear magnetoelectric effects in the noncentrosymmetric phases of BiFeO 3 related ceramics become symmetry allowed and activate by a coupling between the A-site ferroelectric translation and the B-site magnetization via the antiferrodistortive a − a − a − tilt of the oxygen octahedra. 11 Although the linear magnetoelectric effect is symmetry forbidden on a macroscopic scale, the DzyaloshinskiiMoriya mechanism can still be used locally in bulk BiFeO 3 to achieve an electric switching of the spin cycloid. 12 Upon isovalent substitution on the A site, disorder is introduced which eventually leads to a decoherence of the Bi lone pair and a concurrent change in space group from the polar R3c to a nonpolar space group.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Recent computational studies have investigated the effects of epitaxial strain on oxygen vacancies in conventional perovskites. While they predict that the activation energies of these vacancies can be tuned by tenths of an eV under modest strains of a few 3 percent, the initial energies of >2 eV render these changes relatively insignificant at reduced temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…[20,30] Also, it has been theoretically proved that the epitaxial strain modifies the spiral spin structure resulting into the canting of spins and weak ferromagnetism in the multiferroic BFO compounds. [31] In the presently studied films, it is observed that SHI irradiation results in the reduction in structural strain thereby leading to decrease in magnetisation. Also, SHI-induced increase in the amorphised nanoscale defect regions in the film results in the increase in inhomogeneous spin structure and oxygen non-stoichiometry leading to the suppression in magnetisation.…”
Section: Resultsmentioning
confidence: 99%